Pengaruh Budaya Organisasi Terhadap Prestasi Kerja Guru Dengan Profesionalisme Guru Sebagai Variabel Intervening: Studi Pada Guru SMPN 1 Arosbaya Kabupaten Bangkalan - Nurhayati Nurhayati; Chamariyah Chamariyah; Nugroho Mardi (Journal of Management and Creative Business, 2024)
Nurhayati, 2023. The influence of organizational culture on the work performance of teachers at SMPN 1 Arosbaya, Bangkalan Regency which is mediated by professionalism, the Postgraduate Program at Wijaya Putra University. The type of research is explanatory, the research approach used is quantitative, the research sample is 45 respondents. Data analysis uses SPSS and PLS analysis. The aims of this research are: 1) To analyze the influence of organizational culture on the work performance of teachers at SMPN 1 Arosbaya, Bangkalan Regency; 2) To analyze the influence of organizational culture on the professionalism of teachers at SMPN 1 Arosbaya, Bangkalan Regency; 3) To analyze the influence of professionalism on the work performance of teachers at SMPN 1 Arosbaya, Bangkalan Regency; 4) To analyze the indirect influence of organizational culture on the work performance of teachers at SMPN 1 Arosbaya, Bangkalan Regency, which is mediated by professionalism. The results of the research show that: 1) Organizational culture has a significant effect on the work performance of teachers at SMPN 1 Arosbaya, Bangkalan Regency with an original sample value of 0.163; 2) Organizational culture has a significant effect on the professionalism of teachers at SMPN 1 Arosbaya, Bangkalan Regency with an original sample value of 0.267; 3) Professionalism has a significant effect on the work performance of teachers at SMPN 1 Arosbaya, Bangkalan Regency with an original sample value of 0.292; 4) Organizational culture has a significant indirect effect on the work performance of teachers at SMPN 1 Arosbaya, Bangkalan Regency, which is mediated by professionalism with an original sample value of 0.070 and a p-value of 0.009.